Concept mapping sociocultural aspects of cervical cancer prevention among African American women - Carmack, Chakema; Roncancio, Angelica; Coleman, Taylor M.; McKay, Sarah (Frontiers in Public Health, 2024)
Introduction For African American women in Houston, cervical cancer mortality is disproportionate to their racial and ethnic counterparts. Most notably, lack of human papillomavirus (HPV) screening and vaccination as well as late diagnosis increase cervical cancer mortality. However, cervical cancer is largely preventable. While previous research has identified a few social determinants that are specifically related to cervical cancer (e.g., education, income, neighborhood), there may be a host of additional social and cultural factors that contribute to a lack of preventative behavior. Methods The present study used concept mapping to explore sociocultural determinants of cervical cancer prevention beliefs among young African American women. N = 15 African American women, ages 18–25, participated in a group concept mapping session focused on cervical cancer knowledge, beliefs about women’s health, and how their social environment and culture play a role in their conceptualization of cervical cancer prevention. Discussion Five overarching concepts emerged: (1) Screening, (2) Support System, (3) Cervical Cancer 101 (knowledge), (4) Fatalism, and (5) Ease of Prevention. Conclusion The present study highlights the use of concept mapping for prevention science, particularly in exploratory studies for understanding cervical cancer screening barriers, avenues for intervention, and public health messaging. We discuss the findings and implications for public health research in cervical cancer prevention tailored for African American women.